Strategi Retensi Karyawan Berbasis Kesejahteraan Mental - Sinta Dwi Ayu Murbayana; Sunarto SUnarto (Green Publisher Indonesia, 2026)
Employee mental well-being is becoming an increasingly important issue in modern organizations, especially in the face of high turnover rates and increasingly complex work pressures. In a dynamic work environment, psychological factors such as stress, burnout, and lack of emotional support have been shown to affect employee job satisfaction, loyalty, and retention. Therefore, organizations are required to develop retention strategies that not only focus on the financial aspect, but also pay attention to the overall mental well-being of employees. This study aims to analyze mental well-being-based employee retention strategies and examine the role of psychological safety, emotional intelligence in leadership, and mental well-being programs in improving employee retention. This research employs a descriptive qualitative approach through literature study, observations, and interviews with employees and managers in companies that have implemented mental well-being programs. The findings show that good mental well-being enhances job satisfaction, loyalty, and employee retention. Therefore, mental well-being-based retention strategies should be adopted by organizations to enhance productivity and reduce employee turnover rates.